PENEGAKAN HUKUMAN DISIPLIN BERAT BAGI PEGAWAI NEGERI SIPIL (PNS) DALAM PERSPEKTIF HUKUM KEPEGAWAIAN - adrie adrie (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2020)
Civil Servants (PNS) are prohibited from providing support to candidates for President and Vice President by engaging in campaign activities because this is a violation and can be severely disciplined. The purpose of writing this scientific paper is to determine the effectiveness of severe disciplinary penalties according to employment law, and to know the process of severe disciplinary penalties for Civil Servants (PNS). The author uses normative legal research methods with data collection techniques with literature study of legal materials through internet media. The data obtained in this legal research were analyzed using qualitative methods which were presented descriptively which would later obtain meanings and conclusions to answer the problem. The conclusions from the writing of this scientific work are: (1) The absence of effectiveness of severe disciplinary penalties according to the employment law which now applies to Civil Servants (PNS) because in reality, lawlessness continues to occur among Civil Servants (PNS) even though it has been given severe disciplinary punishment so that there must be firmer law enforcement that should be regulated in the employment law; (2) The process of severe disciplinary punishment for Civil Servants (PNS), among others: (a). Civil servants who commit disciplinary violations are examined by the Examining Team consisting of elements of supervision, staffing and direct superiors; (b). LHP is reported in a hierarchical way to officials who have the authority to punish; (c). Preparation and Issuance of Decree for the Dismissal of PNS Discipline by Officials who have the authority to punish; (d). After the issuance of the Decree, then the PNS Discipline SK is handed over to the concerned / Family / through electronic media (Postmark).